Mechanical properties of epoxy resin based on granite stone powder from the Sergipe fold-and-thrust belt composites - Gonçalves,Jorge Antônio Vieira (2014)
This paper studies the mechanical properties including traction, flexion, compression, and hardness characteristics of a composite made from the combination of epoxy resin and granitic stone powder from the fold-and-thrust belt located in the municipality of Nossa Senhora da Glória, in the state of Sergipe, Brazil. Chemical and mineralogical analyses of the stone and analysis by SEM of the particle/matrix interface are performed. Two Granite types, named 53-A and 12-A, were incorporated with different mass percentages of 0%, 30% and 50%, in the polymeric matrix, DGEBA, formed by the Araldite polymer GY 279 and the curing agent Aradur 2963. The test results with 50% show a compression of 79 MPa with a maximum increase of 121% compared with the pure epoxy resin.